Analisis Pengaruh Penerapan Prinsip-Prinsip Good Corporate Governance, Motivasi Dan Budaya Organisasi Terhadap Kinerja Aparatur Pemerintahan (Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Surakarta) - Fuziah, Shifa; , Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2016)
The aim of this research is to know the influence of the Good Corporate Governance Principles, Motivation, and Organizational Culture to the performance of Government Apparatus. The population of this research is all of the government apparatus who work at regional work unit (SKPD) Surakarta. Sampling was done by convenience sampling method and the number of the samples is 119 respondents. The data of this research is primary data by distributing questionnaire. In this research, the analysis equipment that is used is SEM with PLS (Partial Least Square) method. The finding of this research shows that the Good Corporate Governance Principles, Motivation, and Organizational Culture influence to the performance of Government Apparatus.